Mechanical circulatory support devices and their applications: introduction to mechanical circulatory support devices - Presti, Carmen Rosa (Henry Stewart Talks, 2024)
Heart failure, Cardiogenic shock, Extracorporeal Membrane Oxygenation (ECMO), Organ allocation policy, Temporary mechanical circulatory support (MCS), Different types of MCS devices